Factors Influencing Selection and Use of Media for Christian Religious Education Teaching and Learning - Habwenje, Henry Murundu; Okwara, Michael Okello; Otienoh, Ruth; Murundu, Zadock Obuchere (My University, 2017)
Christian Religious Education (CRE) is an important subject for moral and spiritual development. For it to be effectively implemented, teachers have to consider various factors influencing selection and use of media for teaching and learning the subject. Despite its importance, the subject has been taught with minimal use of media. This is because schools are faced with inadequate provision of instructional media which hampers efficient teaching and learning of the subject. The purpose of this study was to determine factors influencing selection and use of media for CRE teaching and learning in Secondary Schools. The study was based on Descriptive Survey Design. The study population consisted of 112 Head teachers, 160 teachers of CRE and 4000 form two students. Random Sampling Technique was used to select 25 Head Teachers. Simple Random Sampling was used to select 53 teachers of CRE and 1333 students. Data was collected using Questionnaires, Teachers’ Interview Schedule, Lesson Observation Schedule and Document Analysis Guide. The study found out that; learner related factors, teacher related factors, available time, availability of media, cost of media and other practical constraints were among factors influencing selection and use of media for Christian religious education teaching and learning. Learners’ abilities were ranked highly as a factor that influenced selection and use of media for CRE teaching and learning as compared to learners’ preferences which were lowly ranked. Teachers’ knowledge and skills on the other hand were also highly ranked as compared to teacher preferences. The study recommended that; school administrators should be inducted on the importance of selection and use of instructional media resources so as to be supportive of their teachers in the effort of availing such resources to schools.
Keywords: Influence; Selection; Use